Moral Development Efforts for Santri at the Hidayatullah Islamic Boarding School - Serliyani Serliyani; Nur Asyiah Siregar (Pusdikra-Publishing.com, 2023)
This study aims to find out how to develop morals for students at the Hidayatullah Tanjung Morawa Islamic Boarding School. this research is a research file. The techniques used in collecting data in the field are through observation, interviews, documentation and literature studies. After the data is obtained, then a descriptive analysis is carried out, so as to get a conclusion. This research concludes that efforts to develop students' morals are implemented in the form of coaching through congregational prayer education, recital wirid, reading the Qur'an properly and correctly, and carrying out other practices of worship, as well as caregivers providing good examples, giving advice, habituation, reprimands in the form of motivation and punishment to foster children who make mistakes with the aim that children do not make the same mistakes because they can harm themselves and others.